RETRACTED: The method of complex biological water treatment in aquaponic recirculation systems - Fedorova Valeria; Shvydchenko Sergey; Dubovik Irina; Shvydchenko Darina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001